What Drives Customer Satisfaction? : Evidence From Customer Fast Food Restaurant Indonesia - Bernarto, Innocentius; Juliana; Djakasaputra, Arifin (School of Business, Bogor Agricultural University (SB-IPB), 2022)
This study aims to examine the positive effect of food quality and brand image on satisfaction and to examine the positive effect of satisfaction on word mouth. Then, tested the moderation of price fairness on the relationship between product quality and brand image and tested the moderation of price fairness on the relationship between satisfaction and word of mouth. Methods of data collection by using a questionnaire. The number of samples in this study were 260 fast food restaurant customers. Data analysis with partial least square-structural equation modeling (PLS-SEM). The results showed that food quality and brand image had a positive effect on satisfaction, then satisfaction had a positive effect on word of mouth. Furthermore, price fairness does not moderate the relationship between product quality and satisfaction, the relationship between brand image and satisfaction, the relationship between satisfaction and word of mouth. Keywords: brand image, food quality, price, satisfaction, word of mouth